The Model of Local Product-Based Economic Empowerment for Development of Micro, Small, and Medium Enterprises (MSMEs) at Yosomulyo Pelangi Market, Metro City, Lampung Province - Binti Munadhiroh; Faizal Faizal; Muhammad Bisri Mustofa (Indonesian Journal of Social Science Education (IJSSE), 2026)
Economic empowerment involves mobilizing resources to develop the economic potential of the community and enhance its productivity, thereby increasing the output of both local human and natural resources. Every village possesses potential—derived from natural, human, and social resources—that can be harnessed. However, low levels of education often prevent this potential from being fully realized; consequently, community development is essential to enhance local capabilities and skills, enabling residents to become self-reliant in establishing businesses and pursuing opportunities. Empowerment strategies can be implemented through programs and activities initiated by individuals, groups, communities, or the government—parties concerned with the community's well-being. The success of local product-based economic empowerment for the development of MSMEs (Micro, Small, and Medium Enterprises) is ultimately evidenced by the achievement of sustainable economic prosperity. This study aims to examine local product-based economic empowerment for MSME development at the Yosomulyo Pelangi Market in Metro City, Lampung Province. Methodologically, this is a qualitative, descriptive field study. Data collection techniques included observation, interviews, and document analysis. Primary data were obtained from the Yosomulyo Pelangi Market organizers and participating vendors, while secondary data were gathered from various sources such as journal articles, books, news reports, and other materials relevant to the research topic. The findings indicate that local product-based economic empowerment for MSME development in Yosomulyo was implemented through stages of awareness-building, capacity strengthening, and execution. The implementation strategy featured the "Pasar Ahad" (Sunday Market) program, held every Sunday morning from approximately 06:00 to 12:00. This sustained development effort successfully fostered local product-based economic empowerment for MSMEs through the Yosomulyo Pelangi Market, resulting in improved community economic welfare and the development of human resources.